Roles of nanoparticles in oil lubrication - Dai, Wei; Kheireddin, Bassem; Gao, Hong; Liang, Hong (Tribology international, 2016)
This review focused on the effects of nanoparticles on tribological performance in oil lubrication. Specifically, chemical, physical, and morphological parameters of nanoparticles were studied through statistical comparison. The influence of those particles on friction and wear was analyzed. Mechanisms of lubrication involving nanoparticles were discussed via collected data in literature. More than a replenishment of the current knowledge, this review facilitates the fundamental understanding of lubrication that enables us to design and develop nanolubricants with superior tribological performance.